The Impact of Baby Massage toward to the Increasing of Baby’s Body Weight Age 3-6 Months at Work District of Puskesmas II Denpasar Timur. - Komang Yogi Triana (Coping: Community of Publishing in Nursing, 2013)
Body weight is used as the best indicator nowadays to know the condition of the nutrition and develop-grow up of the baby. The needed of baby’s nutrient that sufficient well is manifested by increasing the body weight and body length which is appropriate as their age. One of the ways to increase the baby’s body weight safely is by implement the baby massage. The aim of this research is to know the impact of baby massage toward to the increasing of baby’s body weight age 3-6 months at work district of Puskesmas II Denpasar Timur. The method which is used in this research is pre-experimental study (one group pre-test dan post-test design) with t-dependent test. The sample that include in this research are 30 samples with no control group, which is got by purposive sampling technique. Collecting data was using weights tools and observation form that was stacked by researcher. The result of the research is mean point of the sample before massaged is 6083,33 gram, whereas mean point of the sample after massaged is 6338,33 gram. The result of data analyze show there is an impact of the baby’s massage toward to the increasing of baby’s body weight age 3-6 months at work district Puskesmas II Denpasar Timur with Asymp. Sig. (2-tailed) point 0,000 (Asymp. Sig ? 0,05).